2023
DOI: 10.7717/peerj.14771
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus fear of contagion and compliance with social distancing measures: evidence for a sample of a Spanish university community

Abstract: Background Social distancing measures have been one of the core pillars of the strategy against COVID-19 in all the countries. This study aims at understanding what motivates behaviours and compliance with social distancing measures among students and workers from a Spanish public university. Methods We carry out two logistics models considering two different dependent variables: not maintaining social relation with non-cohabiting people an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similar to other study carried out in Spain with university students, participants do not inform of high scores of fears, although they suggest the presence of fear [ 37 ]. The probability of feeling fear of COVID-19 was related to KAP, for example not maintaining social relation with non-cohabiting people [ 47 ]. As previous research had shown [ 25 , 30 , 48 ] participants reporting more knowledge, more positive attitudes or more compliance with preventive strategies also reported feeling more fear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other study carried out in Spain with university students, participants do not inform of high scores of fears, although they suggest the presence of fear [ 37 ]. The probability of feeling fear of COVID-19 was related to KAP, for example not maintaining social relation with non-cohabiting people [ 47 ]. As previous research had shown [ 25 , 30 , 48 ] participants reporting more knowledge, more positive attitudes or more compliance with preventive strategies also reported feeling more fear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher risk perceptions increased the probability of feeling fear [ 29 ]. Being vulnerable or having close vulnerable friends or family members increased the probability of feeling fear as living with a chronically ill family member is related to high negative emotional responses in young people [ 47 ].…”
Section: Discussionmentioning
confidence: 99%